Modification of phosphoinositides by the Shigella effector IpgD during host cell infection - Tran Van Nhieu, Guy; Latour-Lambert, Patricia; Enninga, Jost (Frontiers in Cellular and Infection Microbiology, 2022)
Shigella, the causative agent of bacillary dysentery, subvert cytoskeletal and trafficking processes to invade and replicate in epithelial cells using an arsenal of bacterial effectors translocated through a type III secretion system. Here, we review the various roles of the type III effector IpgD, initially characterized as phosphatidylinositol 4,5 bisphosphate (PI4,5P2) 4-phosphatase. By decreasing PI4,5P2 levels, IpgD triggers the disassembly of cortical actin filaments required for bacterial invasion and cell migration. PI5P produced by IpgD further stimulates signaling pathways regulating cell survival, macropinosome formation, endosomal trafficking and dampening of immune responses. Recently, IpgD was also found to exhibit phosphotransferase activity leading to PI3,4P2 synthesis adding a new flavor to this multipotent bacterial enzyme. The substrate of IpgD, PI4,5P2 is also the main substrate hydrolyzed by endogenous phospholipases C to produce inositoltriphosphate (InsP3), a major Ca2+ second messenger. Hence, beyond the repertoire of effects associated with the direct diversion of phoshoinositides, IpgD indirectly down-regulates InsP3-mediated Ca2+ release by limiting InsP3 production. Furthermore, IpgD controls the intracellular lifestyle of Shigella promoting Rab8 / 11 -dependent recruitment of the exocyst at macropinosomes to remove damaged vacuolar membrane remnants and promote bacterial cytosolic escape. IpgD thus emerges as a key bacterial effector for the remodeling of host cell membranes.